Oligomerization‐driven MLKL ubiquitylation antagonizes necroptosis. (26th October 2021) - Liu, Zikou; Dagley, Laura F; Shield‐Artin, Kristy; Young, Samuel N; Bankovacki, Aleksandra; Wang, Xiangyi; Tang, Michelle; Howitt, Jason; Stafford, Che A; Nachbur, Ueli; Fitzgibbon, Cheree; Garnish, Sarah E; et al.
Abstract: Mixed lineage kinase domain‐like (MLKL) is the executioner in the caspase‐independent form of programmed cell death called necroptosis. Receptor‐interacting serine/threonine protein kinase 3 (RIPK3) phosphorylates MLKL, triggering MLKL oligomerization, membrane translocation and membrane disruption. MLKL also undergoes ubiquitylation during necroptosis, yet neither the mechanism nor the significance of this event has been demonstrated. Here, we show that necroptosis‐specific multi‐mono‐ubiquitylation of MLKL occurs following its activation and oligomerization. Ubiquitylated MLKL accumulates in a digitonin‐insoluble cell fraction comprising organellar and plasma membranes and protein aggregates. Appearance of this ubiquitylated MLKL form can be reduced by expression of a plasma membrane‐located deubiquitylating enzyme. Oligomerization‐induced MLKL ubiquitylation occurs on at least four separate lysine residues and correlates with its proteasome‐ and lysosome‐dependent turnover. Using a MLKL‐DUB fusion strategy, we show that constitutive removal of ubiquitin from MLKL licences MLKL auto‐activation independent of necroptosis signalling in mouse and human cells. Therefore, in addition to the role of ubiquitylation in the kinetic regulation of MLKL‐induced death following an exogenous necroptotic stimulus, it also contributes to restraining basal levels of activated MLKL to avoid unwanted cell death. SYNOPSIS: RIPK3 phosphorylates the necroptotic effector molecule MLKL leading to its oligomerization and translocation to the plasma membrane to kill cells. MLKL becomes multi mono‐ubiquitylated in an oligomerization dependent manner. Forced de‐ubiquitylation of MLKL increases MLKL's cytotoxic potential and confers RIPK3 and necroptotic stimulus independent activation and cell death. UbiCRest analysis shows that MLKL becomes multi mono‐ubiquitylated contemporaneously with activating phosphorylation and translocation to membranes. Analysis of gain and loss of function MLKL mutants indicates that MLKL oligomerization is required for necroptosis induced ubiquitylation. MLKL‐deubiquitylating enzyme (DUB) fusions kill cells more rapidly than MLKL‐catalytically dead DUB fusions and can induce necroptosis without a necroptotic stimulus, suggesting that ubiquitylation serves as a brake on MLKL's cytotoxic potential. Abstract : Mono‐ubiquitylation of the necroptotic effector molecule MLKL promotes its proteasome‐ and lysosome‐mediated turnover to restrains its necroptosis‐inducing activity.